The tale of rare skin condition of the breast: case series: diffuse dermal angiomatosis - Alhamdi, Dooha; Khalil I ALHamdi , Khalil (Journal of Pakistan Association of Dermatologists, 2023)
In clinical practice ,one may come across clinical conditions ,the diagnosis of which, is either overlooked or missed because it is rare so it is not considered by the treating dermatologist or it present with unusual modes regarding the presenting odd features, site affected, patient’s age, predominant sex and time of occurrence, so that, all these points should be considered in order to pick up the proper diagnosis. The ingenuity in clinical practice lie in the diagnosis of challenging unusual cases. Herein we present a case series of female patients presenting with chronic odd skin breast lesions with poor response to treatments to increase the awareness of the dermatologist to such rare condition. To the best of our knowledge, this series is the first one in our country and the region and the fifth worldwide